Biology Learning Models Based on Higher Order Thinking Skills; A Book Research and Development - Jodion Siburian; Ali Sadikin (Postgraduate, University of Mataram, 2024)
This study aims to develop a biology learning model book based on Higher Order Thinking Skills (HOTS) to meet the demand for effective teaching resources in biology education. The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was used to ensure a systematic development process. An initial survey involving 80 respondents revealed that 86.5% of respondents